Determination of parameters of axial symmetrical triple stratified medium after the well yield and the water lowering in regard to elastic properties of weakly penetrating layer - Vu, Pham Loi; Thanh, Nguyen Hoan (Vietnam Journal of Mechanics, 1986)
This paper considers the problem of axial symmetrical filtration to a well in triple stratified medium, which includes the surface stratum, the weakly penetrating layer and the well penetrating main fall horizon. The Lowering of S1, S0, S2 in these starts  sat isfies the system of equations (0.1) with initial and boundary conditions : (0.2), (0.3), (0.4). In this paper the approximate solution of the problem (0.1)- (0.4) with different coefficients water feeding and filtering penetration µ and T1, i = 1, 2 is obtained. The algorithm of restitution for parameters of layer after well yield and water lowering’s is constructed. Using the methods of this work, the results of conculation for example have been presented.